Origins and development of Bologna's dermatological school - Moroni, P... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
The first note on dermatology in Bologna goes back to the year 1200, when Taddeo degli Alderoni introduced the beside teaching. Al the time of the syphilis epidemic the hospital of Saint Job was established to care for these patients by the end of 15th century. During the following centuries many famous physicians were practising and teaching medicine, dermatology included.The greatest advancement of dermatology in Bologna was however in the20th century. Among the prominent dermatologists at least a few deserved tobe mentoned p. Gamberini, S. Giovanni, D. Majocchi and L. Martinotti.
Keywords: dermatologija; Dermatology; Education; Education, medical, continuing; History; Italy; zgodovina medicine